Diversity of Avifauna at the Elephant Training Center Way Kambas National Park - Kamaluddin, Akhmad; Winarno, Gunardi Djoko; Dewi, Bainah Sari (Jurnal Sylva Lestari, 2019)
Avifauna is one of the biodiversity that has a role in the ecosystem, namely as a seed spreader, helps pollination, and as an environmental bioindicator. The Elephant Training Center (PLG) is not only a conservation centre for Sumatran elephants but also serves as a habitat and preserves the diversity of all animals including avifauna species. One form of conservation efforts towards avifauna is to record the diversity of the avifauna species present in that location. This study aims to determine the diversity of bird species found in the Way Kambas National Park PLG. The study was conducted using the point count method at three observation locations: garden area, grassland, and swamp area with three repetitions. The results of the study found 33 species from 21 families (727 individuals) with moderate species diversity values (1 <H '<3). The diversity of bird species affects the existence of some species in a habitat so that it affects the quality of habitat and plays an important role as a bioindicator in an ecosystem. Bird conservation efforts need to be carried out and supported by all parties to maintain the existence of birds in their natural habitat. Keywords: Avifauna, diversity, conservation, national park, elephant training center.